Complementation of an Arabidopsis thaliana mutant that lacks complex asparagine-linked glycans with the human cDNA encoding N-acetylglucosaminyltransferase I. - Gomez, L (1994)
N-Acetylglucosaminyltransferase I (EC 2.4.1.101) initiates the conversion of high-mannose asparagine-linked glycans to complex asparagine-linked glycans in plant as well as in animal cells. This Golgi enzyme is missing in the cgl mutant of Arabidopsis thaliana, and the mutant cells are unable to synthesize complex glycans. Transformation of cells from the mutant plants with the cDNA encoding human N-acetylglucosaminyltransferase I restores the wild-type phenotype of the plant cells. Fractionation of the subcellular organelles on isopycnic sucrose gradients shows that the human enzyme in the complemented cells bands at the same density, 1.14 g/cm3, typical of Golgi cisternae, as the enzyme in the wild-type plant cells. These results demonstrate that complementation results from the presence of the human enzyme in the plant Golgi apparatus, where it is functionally integrated into the biosynthetic machinery of the plant cell. In addition, given the evolutionary distance between plants and mammals and the great diversity of glycoproteins that are modified in each, there is probably no specific recognition between this Golgi enzyme and the polypeptide domains of the proteins it modifies.